Pelatihan dan Pembentukan Posko Tim Pengurusan Jenazah Sesuai Protokol Kesehatan dan Syariat Islam pada Masyarakat Pesisir - Indriono Hadi; Lilin Rosyanti; Akhmad Akhmad; Dwi Yanthi; Syahrianti Syahrianti (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The primary challenge faced during illness is the frequent occurrence of deaths at home. The environment where the deceased is cared for poses a risk of disease transmission and infection. Inadequate cleaning increases the risk of infection, thus families need to understand the techniques of managing the deceased according to health protocols and Islamic Sharia. After training and the formation of male and female corpse management teams, the community can establish corpse management posts and implement corpse management according to health protocols and Islamic Sharia. The method used is persuasive education and practice by combining lectures, question-and-answer sessions, and practical exercises. The implementation took place from September 2 to November 10, 2022, in Bajo Indah Village, Soropia District. The training was attended by 60 participants. The pretest results showed that 71.67% had insufficient knowledge, 18.33% had average knowledge, and 10% had good knowledge. As for the posttest, 1.6% had insufficient knowledge, 56.67% had average knowledge, and 41.67% had good knowledge. The pretest results for practical skills showed that 68.33% had insufficient skills, 30% had average skills, and 1.67% had good skills. Whereas the posttest results showed that 11.67% had insufficient skills, 35% had average skills, and 53.33% had good skills. There was an improvement in participants' knowledge and skills after the training, and the establishment of corpse management posts and teams.